THE CORRELATION BETWEEN READING HABIT AND VOCABULARY MASTERY TOWARD READING ACHIEVEMENT AMONG FIRST YEAR STUDENTS OF SMAN 1 GROGOL - Zahra, Fatimah (LENTERA : Jurnal Pendidikan dan Pengajaran, 2018)
This research is aimed to know whether there is any partial and simultaneus positive significant correlation between reading habit and vocabulary mastery toward reading achievement among first year students of SMAN 1 Grogol or not. Descriptive quantitative method was used as the approach to design and used Multiple Linier Regression and Partial Correlation formula to compute data. The instrument used was questionnaires for reading habit meanwhile test for vocabulary and reading achievement. The result was there is no positive significant partial and simulltaneus correlation between reading habit and vocabulary mastery toward reading achievement among first year students of SMAN 1 Grogol. It is recommended to the teacher in order to know the reading habit of the students and to make the class warm and comfort for learning process to increase the students’ reading achievement.